The Impact of Dynamic Capabilities on Value Creation with Competitive Strategy as a Mediating Variable in Small and Medium Enterprises - Magista Pakpahan, Rheina; Achmad Fauzi, (Technium Social Sciences Journal, 2024)
Small and Medium Enterprises (SMEs) need adaptation to survive. In addition, SMEs also have to be competitive in order to face increasingly fierce competition. SMEs can survive if they can provide added value. Therefore, this study aims to analyze the impact of dynamic capabilities as the ability to be adaptive to value creation with competitive strategy as a mediating variable in Jakarta culinary SMEs. The research was conducted by distributing questionnaires online using purposive sampling to 138 respondents who are owners of Jakarta culinary SMEs. This study uses a quantitative approach, and data is obtained and processed using SEM PLS with SmartPLS 3.0. The results of this study showed that all dimensions of dynamic capabilities, sensing capability, learning capability, integrating capability, and coordinating capabilities have a positive and significant impact on value creation, either directly or mediated competitive strategy.